Anthropology : - Kottek, Conrad Phillip (McGraw Hill, 2013)
Focusing on an increasingly interconnected world, the new Focus on Globalization essays examine topics as diverse as tourism in the ancient and modern worlds, global disease pandemics, world events (including the Olympics and the World Cup), and the expansion of international finance and branding.